تحليل الأفعال الكلامية الإلوكوسية في حوار الرسوم المتحركة الفربي - Nurfajrin Hasan, Sri; Susilo, Joko (Universitas Islam Negeri Raden Mas Said Surakarta, 2022)
This research has two objectives. The first objective is to describe the form of illocutionary speech acts in the dialogue of the cartoon film